The original description of Agama gutturosa Merrem, 1819 and its nomenclatural implication on the genus Bronchocela Kaup, 1827 (Squamata: Agamidae) - Denzer, Wolfgang; Tillack, Frank (Zootaxa, 2024)
We discovered a historical specimen in the collection of the ZMB that fits an overlooked description of Agama gutturosa by Merrem (1819) and possibly represents a specimen on which Seba (1734) based one of his illustrations. Morphologically, the specimen held in the ZMB collection and that described by Merrem (1819) agrees with Bronchocela jubata Duméril & Bibron, 1837 and would constitute a senior synonym of that taxon. An earlier lectotype designation for the taxa Agama cristatella Kuhl, 1820 and Agama gutturosa Merrem, 1820 by Figueroa (2021) is discussed and corrected accordingly. In order to stabilize nomenclatural usage, we consider Agama gutturosa Merrem, 1819 as a nomen oblitum, so that the long standing nomina Bronchocela cristatella (Kuhl, 1820) and Bronchocela jubata Duméril & Bibron, 1837 can prevail.